Análise da colaboração e integração no processo de projeto nas áreas de Arquitetura e Engenharia - Joice Mariana de Assis Teixeira (2022)
In Architecture, Engineering and Construction, collaboration is identified when there is a common vision of the enterprise on the part of the professionals involved and can be analyzed through four resources: people, processes, technology and data. The collaborative work of a team of designers facilitates the integration of different design disciplines, as well as the advance verification of details and information about the construction, making it possible to visualize and control design interferences, in addition to greater control and planning of the enterprise. Collaboration can happen when a traditional design methodology is used, however, it is more costly than in a workflow with coordinated models, as in projects developed with Building Information Modeling (BIM) technology. With this study, we sought to evaluate the integration of architecture and engineering projects and analyze the level of collaboration in the design process of companies in the civil construction sector, considering a workflow with the use, or not, of methodologies such as BIM. For this, a bibliographic survey was carried out on project process configurations, differentiating a traditional and collaborative workflow, and an approach to the use of BIM, as well as an exploratory research on the design process followed in architectural offices of Minas Gerais. Through interviews with these companies, it was possible to evaluate the integration and collaboration between professionals from different areas, thus identifying three collaboration scenarios: the first, companies where there is no collaboration, the second, those where there is collaboration, but the technology BIM is not implemented and, thirdly, companies where there is collaboration and projects are developed in BIM. It was discovered, therefore, that it is possible to develop collaboration without technologies such as BIM, however, a project office that wants to implement it needs to establish a collaborative process, aimed at project integration and interaction between people. Collaboration can happen without the use of Building Information Modeling, as it depends on factors other than the technology used in project development. However, the use of this technology increases collaboration capacity, since it has tools and provides resources that, to be effective, need a collaborative environment.